Strengthening Africa’s capacity to design and implement strategies for food and nutrition security - Babu, Suresh Chandra; Rhoe, Valerie; Temu, Andrew; Hendriks, Sheryl (International Food Policy Research Institute, 2004)
Among the capacity-strengthening challenges the region faces are inadequate in-country capacity, institutional weaknesses, lack of multidisciplinary approaches to problem solving, expatriates’ limited incountry experience, poor governance, and failure to monitor the sustainability of development efforts and to plan for future capacity generation....The current gaps in capacity are known, but as political, environmental, technical, and social contexts change, new needs will arise. Therefore, constant monitoring of organizational and human skills is essential for the identification of future requirements as they unfold. Unless the capacity to design and implement food and nutrition security policy in Africa is developed, strategies and programs will continue to fail and hunger and malnutrition will grow. -- from Text